Conversational Analysis of Language Realizations of Dispreferred Social Acts in Intimate Relationship in the Lion King (1994) Movie - Dinda Anggi Novita Sari; Musli Ariani; I Putu Sukmaantara (FKIP e-PROCEEDING, 2017)
Abstract: This study attempted to investigate the language realizations of dispreferred social acts from an animation movie called the Lion King (1994). The study aimed to give examples on how the English native speakers express their dispreferred social acts naturally performed by the characters with intimate relationship. It is important to know this because different culture between Indonesia and English may lead to different ways of expressing it. The realizations of dispreferred social acts by the characters that have intimate relationship in the movie are performed in mitigated and unmitigated forms. The finding suggests that these characters choose the mitigated form of the language realizations of dispreferred social acts as they want to maintain the social relationship with others. It is better to use the mitigated as those are more polite. In addition, due to their established relationship, they sometimes express their intimate expressions directly which in this case belongs to unmitigated form. Keywords: Adjacency Pairs, Dispreferred Social Acts, Language Realizations of Dispreferred Social Acts, Preference Organization, Conversational Analysis